Frequency of Bacterial Spectrum in Patients Presenting with Acute Appendicitis - Muhammad Abdullah; Muhammad Farhan Saeed; Mirza Sijeel Ahmad; Ibrahim Zafar Gondal; Ghazanfar Jabbar; Sajjad Dost (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To define the incidence of bacterial spectrum in individuals with acute appendicitis. METHODOLOGY: This Descriptive cross-sectional study was conducted at the Department of Surgery, Pak Emirates Military Hospital, Rawalpindi, from November 2023 to April 2024. Statistics were obtained from individuals after written approval. A non-probability consecutive sampling technique was used. 145 Patients who presented with acute appendicitis were included. Non-consenting patients, patients with a history of tuberculosis, pneumonia, urinary tract infection and lower abdominal inflammatory conditions other than appendicitis were excluded. Numerical values were expressed as numbers, mean, and standard deviation and qualitative data were expressed as frequency and percentages. Outcome changers were measured by stratification to determine their efficacy, with a p-value of ?0.05 considered substantial. Statistics were analyzed on SPSS version 20 RESULTS: 145 individuals were involved. The mean age was 43.93±4.28 years. 83 (57.2%) were male and 62 (42.8%) were female. Out of 145 patients with acute appendicitis, the bacterial spectrum showed E. coli (34.5%), Staphylococcus aureus (5.5%), Pseudomonas aeruginosa (30.3%), Klebsiella pneumoniae (11%), Streptococcus (13.8%), Enterococcus saprophyticus (33.1%), and Bacteroides fragilis (38.6%). CONCLUSION: The greater rate of isolation of pathogenic bacteria in patients with acute appendicitis supports its pathogenic role. Gram-negative microorganisms are most common in inflammation of the appendix, equating with gram-positive microorganisms.